1997
DOI: 10.1021/ie960258r
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimum Conditions for the Dissolution of Stibnite in HCl Solutions

Abstract: The Taguchi method has been used to determine optimum conditions for the dissolution of stibnite in HCl solutions. Chosen experimental parameters and their ranges were (i) reaction temperature, 25−70 °C; (ii) solid-to-liquid ratio (in weight), 0.1−0.25; (iii) acid concentration (in weight), 23.71−37%; (vi) mean particle size; 0.1061−0.8426 mm; (v) stirring speed, 200−800 rpm; (vi) reaction time, 5−60 min. The optimum conditions were found to be reaction temperature, 70 °C; solid-to-liquid ratio, 0.125; acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The two performance characteristics were evaluated using the following equations: where SNS and SNL are performance characteristics, n is the number of repetitions performed for an experimental combination, and y i is the performance value of the i th experiment . The results of variance analysis are given in Tables −9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two performance characteristics were evaluated using the following equations: where SNS and SNL are performance characteristics, n is the number of repetitions performed for an experimental combination, and y i is the performance value of the i th experiment . The results of variance analysis are given in Tables −9.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, the performance value corresponding to the optimum working conditions can be predicated by utilizing the balanced characteristic of OA. Under these conditions, the following additive model may be used: where μ is the overall mean of performance value, X i the fixed effect of the quantity level combination used in the i th experiment, and e i the random error in the i th experiment 7 Results of the Analysis of Variance for the Dissolution Values of Zinc a parametersum of squares, S degree of freedom, f variance, S / f variance ratio, F reaction temperature ( °C) 3.36 4 0.84 0.27 stirring speed (rpm) 5.40 4 1.35 0.44 ammonium carbonate concentration (mol) 2.03 4 0.70 0.23 reaction time (min) 3.64 4 0.91 0.30 acidity, pH 0.83 4 0.21 0.06 error 12.25 4 3.06 1 total 28.28 24 a F Table = 6.39 with 95% confidence. …”
Section: Resultsmentioning
confidence: 99%
“…While such vigorous research for commercially viable short-cuts and improvements in the industrial and the business sectors should not surprise anybody, the potential application of Taguchi methods to a wide and increasing range of medical applications might surprise the reader. Taguchi methods have so far been applied to Polymerase Chain Reaction (PCR) technique in biochemistry (Cobb and Clarkson, 1994), optimization of polymerization reactions, evaluation of component separation in Liquid Chromatography analysis by dynamic operating window, functionality evaluation of spray drying medicines, measurement of drug efficacy, prediction of urinary continence recovery among patients with brain disease, health examination and treatment of missing data, diabetes mellitus disease duration and capillary bed's area (Taguchi et al, 2004), determination of optimum conditions for the dissolution of Stibnite in HCl solutions in analytical chemistry (Copur et al, 1997), improvement of haemodialysis quality (Konduk and Ucisik, 1998), and a study of factors influencing patients' length of stay in emergency care units (Rinderer, 1996). Also, the variability of measured value from an oxygen sensor used…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Abali et al studied the optimization of the leaching of dolomite ore in hydrochloric acid solution. Copur et al determined the optimum conditions for the dissolution of stibnite in hydrochloric acid solution. Copur et al revealed the optimum conditions for the dissolution of roasted zinc sulfate in sulfuric acid solution.…”
Section: Introductionmentioning
confidence: 99%